Porosity evolution in organic matter-rich shales (Qingshankou Fm.; Songliao Basin, NE China): Implications for shale oil retention. (August 2021) - Zhang, Penglin; Misch, David; Hu, Fei; Kostoglou, Nikolaos; Sachsenhofer, Reinhard F.; Liu, Zhaojun; Meng, Qingtao; Bechtel, Achim
Abstract: The Songliao Basin is an important hydrocarbon province of Northeastern China and has a long history of conventional oil and gas production. Nowadays, unconventional resource estimation becomes increasingly important and particularly shale oil/gas production from mature source rocks in the Central Depression may be of great relevance for the regional exploration strategy. The Qingshankou Formation is a promising source rock reservoir. However, for shale oil/gas production to be successful, a refined understanding of the distribution of hydrocarbons within the low-permeable rocks, as well as the timing of hydrocarbon expulsion and its linkage to changing pore characteristics, are key requirements. Therefore, a multi-analytical geochemical and porosity study was conducted on a set of 12 oil-prone, alginite-rich samples from a depth range from 200 to 2500 m in order to understand the linkage of burial compaction, hydrocarbon generation and pore evolution. Macro- (>50 nm) and mesopores (2–50 nm) were investigated by a combination of nitrogen gas adsorption/desorption measurements at 77 K and broad ion beam – scanning electron microscopy. The adsorption tests were conducted on samples before and after solvent-extraction in order to study the effects of soluble organic matter (OM) on pore distributions. These data were compared with organic petrographical observations, bulk geochemical parameters before and after extraction, as well as extract yields from the bulk source rock in order to link structural and geochemical changes in the interval from immature to late peak oil mature (0.4–0.9 %Rr). Total SEM-visible macro- and mesoporosity (φBIB ) is generally limited, but a weak trend of total φBIB with quartz contents indicates the importance of brittle minerals for pore preservation. A depth trend towards smaller average pore sizes, higher pore aspect ratios, as well as preferentially bedding-parallel pore orientations reflects burial compaction. An observable deficiency of pores <100 nm in φBIB size distributions, as well as differential BJH mesopore volumes of up to 20% (original vs. extracted), show that pore occlusion by high-molecular weight bitumen changes the apparent pore characteristics particularly for samples from the oil window. A maximum of extractable organic matter (EOM), soluble S2bitumen, S1 normalized to total organic carbon (TOC) contents, as well as saturated vs. aromatic compound ratios determined from source rock extracts, is reached at a vitrinite reflectance of 0.8 %Rr. An interpreted maximum of shale oil in place at ~0.8 %Rr is followed by a decline in these parameters for the samples at slightly higher thermal maturity (0.9 %Rr). This may indicate the onset of hydrocarbon expulsion at >0.8 %Rr, corresponding with a decrease in the differential BJH volume and less visible pre-oil solid bitumen. The gas storage and retention behavior of the investigated shales may abruptly change with ongoing thermal maturation, as matrix pores are liberated from occluding hydrocarbons. Highlights: The hydrocarbon retention properties of the Qingshankou Formation are critical to the evaluation of shale oil potential in the Songliao Basin. A maximum of shale oil stored in occluded mesopores occurs at ~0.8 %Rr. At higher maturities, the occluding hydrocarbons are released, resulting in drastically changing pore characteristics. Differential adsorption tests before and after solvent-extraction enable the quantification of the occlusion effect and the amount of retained hydrocarbons.